Specificity of squamous cell carcinoma antigen (SCCA)‐IgM detection in patients with HCV infection and rheumatoid factor seropositivity. Issue 6 (12th April 2013) - Biasiolo, Alessandra; Tono, Natascia; Zaninotto, Martina; Merkel, Carlo; Fassina, Giorgio; Plebani, Mario; Gatta, Angelo; Pontisso, Patrizia
Abstract: IgM antibodies bound to different cancer antigens have shown recently a higher diagnostic value, compared with the corresponding free molecule, giving rise to a new family of biomarkers. High or increasing levels of Squamous Cell Carcinoma Antigen (SCCA)‐IgM immune complexes were associated with more advanced liver disease and increased risk of development of HCC. Rheumatoid factor (RF) represents a long‐standing problem of interference for immunometric assays. The aim of the present study was to examine the specificity of SCCA‐IgM in relation to the presence of RF reactivity in patients infected with hepatitis C virus (HCV). Sera of 73 patients with cirrhosis, infected with HCV, (mean age ± SD: 66 ± 13 years; M/F: 45/28), including 21 patients with HCC, were studied. SCCA‐IgM immune complexes levels were measured by a commercial ELISA. To evaluate the possible interfering effect of RF, the standard calibrator, positive for SCCA‐IgM, was spiked with serial dilutions of a RF positive or negative serum. SCCA‐IgM immune complexes were positive in 35 out of 73 (48%) patients, while RF activity was found in 10 out of 73 (14%) patients. Patients with cirrhosis with RF activity had significantly higher levels of SCCA‐IgM, compared to RF negative cases; however, no significant correlation between SCCA‐IgM and RF values was observed. In samples created artificially the same results in terms of reactivity for SCCA‐IgM were obtained, regardless of the presence of RF activity. These findings support the lack of correlation between the two parameters found in sera of patients infected with HCV. J. Med. Virol. 85: 1005–1008, 2013. © 2013 Wiley Periodicals, Inc.